2020
DOI: 10.21203/rs.3.rs-32186/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of the efficacy of five standard topical hemostats: a study in porcine liver and spleen models of surgical bleeding

Abstract: Background: Several topical hemostats are available to help control surgical bleeding. Cutanplast is a highly absorbent and porous gelatin product that is available in Fast sponge and powder forms. This study investigated the hemostatic efficacy of Cutanplast Standard and Fast gelatin sponge and powder and Emosist oxidized regenerated cellulose (ORC) gauze in porcine liver and spleen surgical bleeding models.Methods: Cutanplast Standard and Fast gelatin sponge and Emosist ORC gauze were tested in liver abrasio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…A recent comparative study in porcine liver and spleen bleeding models showed both powder and sponge gelatin-based mechanical hemostats to be effective for parenchymal surgical bleeding, but powder to be more suitable for mild diffuse bleeding. [27]…”
Section: Discussionmentioning
confidence: 99%
“…A recent comparative study in porcine liver and spleen bleeding models showed both powder and sponge gelatin-based mechanical hemostats to be effective for parenchymal surgical bleeding, but powder to be more suitable for mild diffuse bleeding. [27]…”
Section: Discussionmentioning
confidence: 99%
“…A novel technique for port closure with the potential to reduce operating times and decrease the incidence of bleeding and herniation from the insertion of port-site trocars has been developed using a sterile absorbable gelatin sponge with strong hemostatic properties (Cutanplast® Plug) [26,27]. The technique has particular relevance to the obese population and is especially advantageous when access for the closure of port-site incisions by suturing is very difficult.…”
Section: Key Pointsmentioning
confidence: 99%
“…The company's products are manufactured and distributed according to ISO Classifications and European Union Directives. One of their products is Cutanplast®, a novel sterile resorbable gelatin with a powerful hemostatic effect [26,27].…”
Section: Trocar Port-site Closure Using Cutanplast Biodegradable Plugsmentioning
confidence: 99%
See 1 more Smart Citation